2005
DOI: 10.1039/b502427g
|View full text |Cite
|
Sign up to set email alerts
|

Distorted five-fold coordination of Cu2+(aq) from a Car–Parrinello molecular dynamics simulation

Abstract: The solvation shell structure and dynamics of a single Cu2+ ion in a periodic box with 32 water molecules under ambient conditions has been investigated using Car-Parrinello molecular dynamics simulations in a time-window of 18 ps. Five-fold coordination with four equidistant equatorial water molecules at 2.00 A and one axial water molecule at 2.45 A from the Cu2+ ion is found. A "hole" without water molecules is found on the opposite side of the axial water. The ion-water bonding character for the equatorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
72
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 66 publications
11
72
0
1
Order By: Relevance
“…On the other hand, Rode and coworkers [19][20][21][22][23] obtained almost exclusively a sixfold coordinated copper(II) with Jahn-Teller distortion of the octahedral ligand field in the presented QM/MM calculations at both Hartree-Fock and B3LYP levels of theory. The only exception found by Rode and coworkers was a resolution of identity BP86 (nonhybrid DFT) calculation [21], which is similar to the BLYP functional calculations employed in the CP simulations [13,18], and which yielded a fivefold to sixfold coordination ratio of ca 60:40 [21]. Concluding that, without the inclusion of exact exchange, the fivefold coordination is becoming more preferred [21].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, Rode and coworkers [19][20][21][22][23] obtained almost exclusively a sixfold coordinated copper(II) with Jahn-Teller distortion of the octahedral ligand field in the presented QM/MM calculations at both Hartree-Fock and B3LYP levels of theory. The only exception found by Rode and coworkers was a resolution of identity BP86 (nonhybrid DFT) calculation [21], which is similar to the BLYP functional calculations employed in the CP simulations [13,18], and which yielded a fivefold to sixfold coordination ratio of ca 60:40 [21]. Concluding that, without the inclusion of exact exchange, the fivefold coordination is becoming more preferred [21].…”
Section: Introductionmentioning
confidence: 74%
“…According to Pasquarello et al [13], the fivefold coordination was confirmed also by the neutron diffraction methods. Fivefold coordination was also obtained from the (nonhybrid DFT) CP molecular dynamics performed by Amira et al [18]. On the other hand, Rode and coworkers [19][20][21][22][23] obtained almost exclusively a sixfold coordinated copper(II) with Jahn-Teller distortion of the octahedral ligand field in the presented QM/MM calculations at both Hartree-Fock and B3LYP levels of theory.…”
Section: Introductionmentioning
confidence: 97%
“…22,23 Surprisingly, the coordination environment even for the simplest hydrated Cu(II) ion has been the subject of extensive debate in recent years. 21,[24][25][26][27][28][29][30][31][32] The most recent X-ray absorption studies (EXAFS and XANES) of aqueous solution of Cu(II), 26 as well as theoretical calculations performed by us 30 and others, 31,32 showed that the [Cu(aq)] 2+ ion can be represented as a five-coordinate square-pyramidal structure with one elongated axial water molecule. Despite the flexibility of the coordination geometry, Cu 2+ is one of the most strongly coordinated divalent transition metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Two independent Car-Parrinello molecular dynamics (MD) simulations performed [using the BLYP functional and a plane-wave basis set] predicted a 5-fold coordination for Cu 2+ . 31,32 In contrast, QM/ MM MD simulations [employing HF, B3LYP, and MP2 levels of theory with the double-valence basis set for water and the comparable LANL2DZ basis set for Cu 2+ ] resulted in predicting exclusively the Jahn-Teller distorted 6-fold coordinated species. [34][35][36][37] A study of the hydration of Cu 2+ by a small number of water molecules may be an important step toward a better understanding of peculiar solvation effects in bulk water.…”
Section: Introductionmentioning
confidence: 99%